PROFIL PENGGUNAAN OBAT HERBAL SEBAGAI ALTERNATIF PENGOBATAN ASAM URAT PADA MASYARAKAT KELURAHAN PANDANG-PANDANG RT 02 RW 07 KABUPATEN GOWA PROVINSI SULAWESI SELATAN - Suhartini Suhartini; Yusriyani Yusriyani (Jurnal Kesehatan Yamasi Makassar, 2022)
Research has been conducted in Kelurahan Pandang-Pandang Rt 02 Rw 07 Gowa Regency in April-August 2021 on The Profile of The Use of Herbs as An Alternative To Uric Acid Treatment of The Village Community Pandang-Pandang Rt 02 Rw 07 Gowa Regency. This research is a descriptive type of research by conducting a direct interview to the community in The Village Of View Rt 02 Rw 07 with 43 respondents selected based on accidental sampling techniques. The results showed that there are 5 types of plants used by the community of Kelurahan Pandang-Pandang Rt 02 Rw 07 Gowa Regency as an alternative treatment of uric acid, namely bay leaves, Chinese betel leaves, soursop leaves, mengkudu fruit, centella asiatica. The herbal plant used as an alternative to the treatment of uric acid is the most soursop leaves that is 30.23%. Metode processing is most widely used is in boiled 79,06%.